Answer:
B and E
Explanation:
Given the rational expression
← factorise the denominator
2x² - 32 ← take out a common factor of 2 from each term
= 2(x² - 16) ← (x² - 16) is a difference of squares
= 2(x - 4)(x + 4)
The expression can now be written as
![(x-7)/(2(x-4)(x+4))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6yvmctcygzhq2kjto23r7atbpfu83c1mix.png)
The denominator of the expression cannot be zero as this would make the expression undefined. Equating the denominator to zero and solving gives the values that x cannot be.
2(x - 4)(x + 4) = 0
Equate each factor to zero and solve for x
x - 4 = 0 ⇒ x = 4
x + 4 = 0 ⇒ x = - 4
These are the values of x that make the expression undefined.
x = 4 → B
x = - 4 → E